Study on Dynamics of Planetary Gear Transmission Considering Backlash - Da Min; Guangming Zou; Xingdong Wang; Wei Tang (Jixie chuandong)
Taking cylindrical spur gear as study object，a nonlinear dynamics model of planetary gear transmission system is established by using mass concentration method. Four influences factors，namely backlash，time-varying meshing stiffness，meshing damping and comprehensive meshing error，are considered in the model，the dynamics equations corresponding to the model are listed and solved by the fourth-order Runge Kutta method. By changing the size of the backlash，the response states of the system under different backlash sizes are obtained. Finally，the time displacement image of relative position error，phase plane diagram and FFT spectrum are used to reflect the effect of specific backlash size on gear vibration response.